2012
DOI: 10.3354/ame01562
|View full text |Cite
|
Sign up to set email alerts
|

Interactive climate change and runoff effects alter O<sub>2 fluxes and bacterial community composition of coastal biofilms from the Great Barrier Reef

Abstract: Global (i.e. ocean warming) and local (i.e. land runoff) anthropogenic disturbances affect coastal coral reefs worldwide. Terrestrial runoff, leading to reduced light and increased nutrient availability, may have interactive effects with ocean warming in promoting shifts in benthic communities. Because microbial biofilms rapidly reflect environmental changes, we investigated the quantitative (C, N and chlorophyll a contents) and qualitative (microbial community composition) parameters and metabolic responses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 83 publications
(114 reference statements)
1
16
0
Order By: Relevance
“…Our findings suggest that the parameters Chl a and DOC, both found at high concentrations inshore during the wet season, were the main drivers in spatiotemporal bacterial community shifts. This is in concordance with previous studies on biofilms from local aquaria studies (53) and midshelf reefs from the GBR (46) and temperate marine bacterioplankton (16,19,23).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Our findings suggest that the parameters Chl a and DOC, both found at high concentrations inshore during the wet season, were the main drivers in spatiotemporal bacterial community shifts. This is in concordance with previous studies on biofilms from local aquaria studies (53) and midshelf reefs from the GBR (46) and temperate marine bacterioplankton (16,19,23).…”
supporting
confidence: 82%
“…Several microbial bioindicator studies repeatedly reconfirmed the aforementioned phylogenetic groups with similar responses (24,(51)(52)(53). Of particular relevance were the decreasing relative abundance of Alphaproteobacteria (mostly Roseobacter) and the concomitant increase in Bacteroidetes (mostly Flavobacteriaceae) detected in biofilms in response to increased water temperature (47,53), partial CO 2 pressure (pCO 2 ) (51), and nitrate (53).…”
mentioning
confidence: 96%
“…Recently, it was shown that the abundance of surface-associated MRC bacteria is decreased while that of Bacteroidetes is increased in response to increases in environmental temperature or elevated partial CO 2 pressure (pCO 2 )-induced ocean acidification (322,324). Similarly, the abundance of planktonic Bacteroidetes also increases in response to increased temperature and/or CO 2 content (and thus decreased pH) in both mesocosms and natural seawater environments (850)(851)(852).…”
Section: Marine Roseobacter Clade Bacteria and Bacteroidetes In Surfamentioning
confidence: 99%
“…Environmental factors play important roles in determining microbial surface colonization events (47,60,(322)(323)(324). In general, the interaction of microbial cells with the substratum surface under specific physicochemical and nutritional conditions at the seawater-surface interface likely contributes substantially to the initiation and success of microbial surface colonization in marine environments.…”
Section: Microbial Sensing and Signaling In Surface Colonization And mentioning
confidence: 99%
“…After 3 h incubation under ambient light, incubation chambers were retrieved and a water subsample was directly analyzed for TA (as described above). Oxygen concentration was determined in each incubation chamber including two blank incubations per treatment (to correct for seawater production/respiration) with a hand-held dissolved oxygen meter (HQ30d, Hach) as described elsewhere (Uthicke and Fabricius 2012;Witt et al 2012). Light intensities of incubation conditions were recorded by two light loggers (Odyssey, New Zealand) each at control and seep site.…”
Section: Calcification and Photosynthesismentioning
confidence: 99%